Oxidative weathering of a copper sulphide ore and its influence on pulp chemistry and flotation. (December 2016) - Jacques, S.; Greet, C.J.; Bastin, D.
Highlights: Study of the influence of pulp chemistry on partially oxidised sulphide ores. A copper sulphide ore was artificially oxidised to various lengths of time. Grinding-flotation tests using different grinding media alloys were completed. The results reveal that as oxidation progressed the copper metallurgy deteriorated. The right grinding chemistry mitigated the negative impacts of ore oxidation. Abstract: The influence of grinding chemistry on the flotation behaviour of sulphides minerals has been widely studied. However, its influence on partially oxidised sulphide ores is not well documented. Various oxidation events can affect a sulphide ore, either during in situ weathering of an ore body or during the different extraction and processing stages (mining operations, stockpiling, crushing, milling and flotation). In this study, a hypogene copper sulphide ore was artificially oxidised to various lengths of time by percolating a small quantity of acidic ferric sulphate solution inoculated with a mixed bacterial culture through packed columns. For each time interval a series of grinding-flotation tests using different grinding media alloys was completed. The grinding and flotation chemistry were compared and linked to the flotation behaviour of the ore samples. The results reveal that as oxidation progressed the copper metallurgy deteriorated. However, the deleterious effects of oxidation could be partially overcome through the application of the right grinding chemistry.